2023
DOI: 10.1002/adma.202207443
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered 3D Skeletal Muscle Model Reveals Complement 4b as a Cell‐Autonomous Mechanism of Impaired Regeneration with Aging

Abstract: A mechanistic understanding of cell-autonomous skeletal muscle changes after injury can lead to novel interventions to improve functional recovery in an aged population. However, major knowledge gaps persist owing to limitations of traditional biological aging models. 2D cell culture represents an artificial environment, while aging mammalian models are contaminated by influences from non-muscle cells and other organs. Here, a 3D muscle aging system is created to overcome the limitations of these traditional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 96 publications
0
13
0
Order By: Relevance
“…53 Previously, we found that, while young muscle constructs showed increased MPC amplification 1 day post injury (DPI), increases in MPC number were only detected in aged muscle constructs until 7 DPI. 53 More importantly, the aged muscle constructs recapitulated the regenerative responses of aged muscles to different interventions, including EVs. 53 Aged muscle constructs were prepared by culturing aged MPCs in a 3D hydrogel mixture of fibrin and Matrigel and maintained in a PDMS chamber containing two posts that provided physical anchors for attachment to induce the development of aligned myotubes (Figure 4A, S5A, S5B).…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…53 Previously, we found that, while young muscle constructs showed increased MPC amplification 1 day post injury (DPI), increases in MPC number were only detected in aged muscle constructs until 7 DPI. 53 More importantly, the aged muscle constructs recapitulated the regenerative responses of aged muscles to different interventions, including EVs. 53 Aged muscle constructs were prepared by culturing aged MPCs in a 3D hydrogel mixture of fibrin and Matrigel and maintained in a PDMS chamber containing two posts that provided physical anchors for attachment to induce the development of aligned myotubes (Figure 4A, S5A, S5B).…”
Section: Resultsmentioning
confidence: 95%
“…53 More importantly, the aged muscle constructs recapitulated the regenerative responses of aged muscles to different interventions, including EVs. 53 Aged muscle constructs were prepared by culturing aged MPCs in a 3D hydrogel mixture of fibrin and Matrigel and maintained in a PDMS chamber containing two posts that provided physical anchors for attachment to induce the development of aligned myotubes (Figure 4A, S5A, S5B). After 14 days of myotube induction, muscle constructs produced twitch and tetanic contractions upon 1 and 40 Hz electric stimulation, respectively (Figure S5C).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations